Pelaksanaan Pengadaan Barang/Jasa Secara Elektonik (E-Procurement) Pada Satuan Kerja Pelaksanaan Jalan Nasional Provinsi Kalimantan Tengah - Rooswandy Juniawan; Muhamad Yusuf; Junaidi Junaidi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This research aims to analyze the implementation and identify the inhibitory factors of the Implementation of the Procurement of Goods /Services Electonic (e-procurement) in the National Road Implementation Task Force of Central Kalimantan Province. The desired target in the study, the researchers gave a limitation of the problem the implementation of electronic tenders for construction workers (roads/bridges) in the National Road Implementation Task Force of Central Kalimantan Province. The research approach in this study is a type of qualitative descriptive that aims to describe the complexity and dynamic in the procurement of electronic goods/services. Data collection was conducted through observations, interviews, and documentation. The interviewees were the head of the task force, the commitment-making officer, the task force assistant, the treasurer, and other employees related to the electoral auction in the Central Kalimantan Province National Road Implementing Task Force. The results of the study show the conclusion that the implementation of procurement of goods /services electronically in the national road implementation taskforce of Central Kalimantan Province has been carried out for the last few years. All stages of the auction are electonic through a long process of 14 stages that all transparent using a system that can be accessed for the public. However, the factor of inhibiting the implementation of electronic procurement of goods /services (e-procurement) in the national road implementation taskforce of Central Kalimantan Province is 1) HR, namely the lack of expertise in running the application of Electronic Procurement System (SPSE) as well as the lack of employees who have a Certificate of Procurement of Service Goods which is an absolute requirement to become Pokja Election / Procurement Officer. 2) Technology, internet network capacity that causes internet access speed to be slow.